The Equivocal Role of Th17 Cells and Neutrophils on Immunopathogenesis of Leishmaniasis - Gonçalves-de-Albuquerque, Suênia da C.; Pessoa-e-Silva, Rômulo; Trajano-Silva, Lays A. M.; de Goes, Tayná Correia; de Morais, Rayana C. S.; da C. Oliveira, Cíntia N.; de Lorena, Virgínia M. B.; de Paiva-Cavalcanti, Milena (Frontiers in Immunology, 2017)
Advances in the understanding of leishmaniasis progression indicate that cellular interactions more complex than the Th1/Th2 paradigmdefine the course of infection. Th17 cells are a crucial modulator of adaptive immunity against Leishmania parasites acting mainly on neutrophil recruitment and playing a dual role at the site of infection. This review describes the roles of both these cell typesin linking innate defenseresponses to the establishment of specific immunity. We focus on the Th17–neutrophil interaction as a crucial component of anti-Leishmania immunity, and the clinical evolution of cutaneous or visceral leishmaniasis.To date, information obtained through experimental models and patient evaluations suggests that the influence of the presence of interleukin (IL)-17 (the main cytokine produced by Th17 cells) and neutrophilsduring Leishmania infections is strictly dependent on the tissue (skin or liver/spleen) and parasite species. Also, the time at which neutrophils are recruited, and the persistence of IL-17 in the infection microenvironment, may also be significant. A clearer understanding of these interactionswill enable better measurement ofthe influence of IL-17 and its regulators,and contribute to the identification of disease/resistance biomarkers.